A novel prostaglandin is the major product of arachidonic acid metabolism in rabbit heart. - Isakson, P C (1977)
The prostaglandins (PGs) released from the heart have generally been characterized as resembling PGE by bioassay techniques. The major PG formed from [14C]arachidonate (C20:4) by the isolated perfused rabbit heart has chromatographic mobility similar to that of PGE2 in most solvent systems. However, additional analysis of this radioactive "PGE" peak suggests that two substances are formed by the heart and migrate like PGE2: one has chemical properties similar to those of authentic PGE2 and the other is a novel PG. The unknown compound is the major PG formed by the heart from either exogenous arachidonate or hormonal stimulation of PG biosynthesis. The novel PG produced by the heart may be identical with either 6(9)-oxy-PGF or 6-keto-PGF1 alpha.